Site specific differences in food and feeding biology of Nemipterus japonicus (Bloch, 1791) along Indian coast - Sreekanth, G.B.; Pazhayamadom, Deepak G; Chakraborty, Sushanta Kumar; Jaiswar, Ashok Kumar; Renjith, R.K; R, Ratheesh Kumar; A, Anuraj (Indian Journal of Fisheries, 2012)
Feeding biology of populations of a typical demersal carnivorous fish species, Nemipterus japonicus (Japanese threadfin bream) from four different locations of India was studied on the basis of percentage number, percentage weight and occurrence of food items. The basic indices viz., percentage number, gravimetric index and percentage occurrence were used to calculate preference indices like the index of relative importance (IRI) and index of preponderance (IP). Percentage similarity index (PSI) and dietary breadth (DB) were used for investigating the site specific variation in food and feeding biology from 4 sites viz., Mumbai and Cochin from the west coast and Chennai and Kakinada from the east coast of India. Some important food items like squid, lizard fish, Solenocera sp. and polychaetes which were common in other locations, were not reported from Kakinada samples. The PSI and DB indicated marked variations in feeding biology of populations from different sites on the east and west coast. Similarity index was maximum between Mumbai and Cochin while the second highest value was between Kakinada and Chennai. A narrow spectrum of food items was observed for Kakinada and Chennai populations in contrast to a broader spectrum for Cochin and Mumbai populations. The west coast individuals revealed abundance of shrimps, while east coast individuals showed abundance of crabs in the diet. The analysis reflected a coastwise variation in the food items of the species.